## Step 1

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T T T T T T T F T T T F T F T T T F T T F F T T F F F T T F F T T F T F F F T F F F T F F F T F F F F F F F

## Step 2

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T T F T T F T T T F T F T T T F T F T T F T F F T T F F T F T F T F F T T F T F T F T F T F F T F T T F F F T F T F F F T F F F F T F F T F

## Step 3

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T T F T T T F T T T F T F T T T T F T F T T F T F F F T T F F T F T F F T F F T T F T F T T F T F T F F T F T T T F F F T F T F T F F T F F F F T F T F T F

## Step 4

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T T T F T T T F T T T F T T F T T T T F T F T T F F T F F F T T F F T F F T F F T F F T T F F T F T T F T F T F F F T F T T T F F F T F F T F T F F T F F F F F T F T F T F

## Step 5

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T F T T F T T T F T T T F F T T F T T T T F T F T T T F F T F F F T T F F T T F F T F F T F F T T T F F T F T T F T F T F T F F T F T T T F F F T T F F T F T F F T F F F T F F T F T F T F

## Step 6

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T F T T F T T T T F T T T F F T T F T T T T T F T F T T T F F T F F F F T T F F T T F F T F F T T F F T T T F F T F T T F F T F T F T F F T F T T T T F F F T T F F T F T F F F T F F F T F F T F T F T T F

## Step 7

 P Q R ~ ( ~ ( P ↔ ( ~ P ∨ Q ) ) → ~ R ) T T T F F T T F T T T T F T T T F F F T T F T T T T T F T F T T T T F F T F F F F T T F F F T T F F T F F T T F F T T T T F F T F T T F F T F T F F T F F T F T T T T F F F T T T F F T F T F F F T F F F F T F F T F T F T T F